The adventures of Hergé - Bocquet, José-Louis (Drawn & Quarterly ; Distributed in the United States by Farrar, Straus & Giroux, 2011)
Presents a biography in graphic novel format about the life of Tintin's creator, Georges Prosper Remi, from his childhood and meeting with the editor of "XXe Siècle" to the accusations about ties to the Nazis and his relationship with Fanny Vlamynck.